ABORIGINAL EDUCATION AND ANTI‐RACIST EDUCATION: BUILDING ALLIANCES ACROSS CULTURAL AND RACIAL IDENTITY - St. Denis, Verna (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
A critical race analysis could provide both Aboriginal students and their university student advisors with knowledge to understand and potentially challenge the effects and processes of racialization that have historically, legally, and politically divided Aboriginal communities and families. Coalition and alliances can be made within and across the diversity within Aboriginal and non‐Aboriginal peoples’ lives through a common understanding and commitment to anti‐racist education. A critical anti‐racist education could provide a foundation to forge alliances between diverse Aboriginal and non‐Aboriginal communities in a common search for social justice in education. Key words: coalition, alliance, social justice, racialization Une analyse critique de la race pourrait fournir aux étudiants autochtones et à leurs conseillers universitaires des connaissances qui leur permettraient de comprendre et peut‐être de remettre en question les effets et les processus de racialisation qui, à travers l’histoire et sur les plans juridique et politique, ont divisé les communautés et les familles autochtones. Des coalitions et des alliances peuvent être formées au sein des peuples autochtones et non autochtones grâce à une compréhension et à une promotion communes de l’éducation antiraciste. Une éducation antiraciste faisant place à l’analyse critique pourrait fournir une base pour la formation d’alliances entre les communautés autochtones et non autochtones dans un souci commun de justice sociale dans le domaine de l’éducation. Mots clés : coalition, alliance, justice sociale, racialisation